Faktor Yang Berhubungan Dengan Prilaku Pencegahan Covid-19 Pada Ibu Hamil - Dita Selvia Aditia; Putri Hilwati Muri (Jurnal Ilmu Kebidanan, 2023)
Background: Indonesia prioritizes the high number of maternal and child health, the main thing is in the group of pregnant women, giving birth and babies in the puerperium marked by high Maternal Mortality Rates (MMR) and Infant Mortality Rates (IMR). Poor understanding of the disease and the process of disease transmission can contribute to the increase in the number of cases of the disease. To find out the Factors Associated with the Behavior of Covid-19 Prevention in Pregnant Women in Bayas Jaya Village, Way Khilau Pesawaran District. The method used is analytic correlation, namely analytic research from the results of correlation with the design of the study using cross sectional to find out how far the relationship between the independent variables and the dependent variable is. Respondents in this study were pregnant women in the village of Bayas Jaya. The data used is primary data through filling out questionnaires. In this analysis the statistical tests used were the Chi Square test and multiple logistic regression analysis. The research results show that from the relationship test there is a significant relationship with the knowledge variable with a p value of 0.001 and the attitude variable with a P value of 0.005, while there is no significant relationship with the work variable with a p value of 0.057. The most dominant variable test results are the knowledge variable with a p value of 0.013 and an OR value of 3.517, which means that if the mother's knowledge is lacking, then pregnant women do not carry out the Covid 19 prevention behavior 3.5 times. The conclusion from this study is that there is a significant relationship between knowledge and attitude with the dominant variable is on the knowledge variable.